Business response patterns t sustainable development issues: an appraisal of corporate social responsibility initiatives in Nigeria (2014)
In recent years, advocates of Corporate Social Responsibility (CSR) have argued that CSR should be a strategic engine for long-term corporate profits and responsible social development (Berkhout, 2005). The corporate world has therefore embraced sustainable development as the new paradigm of development. Due to this paradigm shift, some corporate organizations have redirected their CSR initiatives to focus on development issues. The basic assumption in this paper is that business as a social agent has both the economic and social power to set standard and targets that will respond to social demands and address development challenges of the 21st century. So, based on the stakeholder theory and The Natural Step Framework, the paper investigates business approaches to sustainable development issues in a developing society. Specifically, it highlights the extent to which selected organisations in the telecommunications, oil and gas, food and beverages, cement manufacturing and banking sectors have embarked upon responsible and sustainable activities in Nigeria. Moreover, challenges which affect effective implementation of CSR policies aimed at sustainability are revealed in this work. The paper concludes by advocating an integrated transformative approach to CSR. The paper contributes to the on-going debate on social responsibility of business and sustainability agenda in developing economies.